An Overview of the Deadly Effects of Anabolic-Androgenic Steroids: Clinical Cases and Scientific Insights - Maciej Mossakowski; Martyna Kaźmierczak; Marta Jajczak; Jakub Parys; Agnieszka Mikosińska; Patrycja Kałuziak; Aleksandra Witek; Mateusz Litwin; Stanisław Jesionek (Quality in Sport)
Background: Anabolic-androgenic steroids (AAS) are widely used for performance enhancement, but their misuse, particularly in bodybuilding and professional sports, poses significant health risks. While AAS have legitimate medical applications in treating certain hormonal disorders, abuse of these substances can lead to severe and often irreversible health consequences.